2018
DOI: 10.1186/s12861-018-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Short term optical defocus perturbs normal developmental shifts in retina/RPE protein abundance

Abstract: BackgroundMyopia (short-sightedness) affects approximately 1.4 billion people worldwide, and prevalence is increasing. Animal models induced by defocusing lenses show striking similarity with human myopia in terms of morphology and the implicated genetic pathways. Less is known about proteome changes in animals. Thus, the present study aimed to improve understanding of protein pathway responses to lens defocus, with an emphasis on relating expression changes to no lens control development and identifying bidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 143 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…Most notably, photoreceptor proteins involved in the generation of the electroretinogram response were negatively correlated with refraction across negative and positive lens groups at this early time-point [26]. Furthermore, changes in the expression of ion transporters, including Na/K/ATPase and other ATP-powered pumps, were evident at later time-points, consistent with the expected link between cell activity, ion transport and associated metabolic needs during periods of altered eye growth [25][26][27][28][29]. Concurrent changes in the expression of immune (particularly complement-coagulation) and oxidative stress genes and proteins previously linked to maculopathy and choroidal neovasculatization suggests that downstream signalling cascades during periods of altered growth may combine with structural stress to predispose secondary pathology with age in high myopia [26,27,[29][30][31].…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Most notably, photoreceptor proteins involved in the generation of the electroretinogram response were negatively correlated with refraction across negative and positive lens groups at this early time-point [26]. Furthermore, changes in the expression of ion transporters, including Na/K/ATPase and other ATP-powered pumps, were evident at later time-points, consistent with the expected link between cell activity, ion transport and associated metabolic needs during periods of altered eye growth [25][26][27][28][29]. Concurrent changes in the expression of immune (particularly complement-coagulation) and oxidative stress genes and proteins previously linked to maculopathy and choroidal neovasculatization suggests that downstream signalling cascades during periods of altered growth may combine with structural stress to predispose secondary pathology with age in high myopia [26,27,[29][30][31].…”
Section: Introductionmentioning
confidence: 66%
“…Gene-level statistics implicated thousands of transcripts during lens-induced myopia induction, but only six transcripts under hyperopia induction conditions. Due to the single-gene focus of the original analysis, it remains unclear whether similar gene pathways are implicated at early time-points in the lens myopia and hyperopia models, as reported in our previous 6 h proteomics [26,28], or in transcriptome measures at later time-points [29,30]. Thus, we re-analysed Stone et al's data using the Gene Set Enrichment Analysis (GSEA) algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…TPMPA) to inhibit the response to FD by inhibiting axial elongation and vitreous chamber depth 16 , 125 128 . Downregulation of GABA and glycine in retinal tissue has also been seen in normally growing chicks over a 48 h period 129 , whereas the same study observed an increase in GABA signaling proteins in the same 6–48 h period when chicks wore negative lens wear and during which refractive compensation was achieved 129 .…”
Section: Discussionmentioning
confidence: 94%
“…Thus, the methods for protein quantification have been used increasingly nowadays, with the most popular being the label-free technique and chemical labeling. The LF method was used, among others, to analyze the vitreous and retina from both humans [10,32] and animals [15,21,27]. In turn, chemical tags found application in the analysis of the proteomic profiles of the retina, vitreous and aqueous humor.…”
Section: Proteomicsmentioning
confidence: 99%